Differences between the effects of plant species and compartments on microbiome composition in two halophyte Suaeda species. Issue 5 (2nd May 2022) - Peng, Mu; Wang, Chao; Wang, Zhiyong; Huang, Xiufang; Zhou, Fangzhen; Yan, Shaopeng; Liu, Xiaopeng
ABSTRACT: Root-related or endophytic microbes in halophytes play an important role in adaptation to extreme saline environments. However, there have been few comparisons of microbial distribution patterns in different tissues associated with halophytes. Here, we analyzed the bacterial communities and distribution patterns of the rhizospheres and tissue endosphere in two Suaeda species ( S. salsa and S. corniculata Bunge) using the 16S rRNA gene sequencing. The results showed that the bacterial abundance and diversity in the rhizosphere were significantly higher than that of endophytic, but lower than that of bulk soil. Microbial-diversity analysis showed that the dominant phyla of all samples were Proteobacteria, Actinobacteria, Bacteroidetes, Acidobacteria and Firmicutes, among which Proteobacteria were extremely abundant in all the tissue endosphere. Heatmap and Linear discriminant analysis Effect Size (LEfSe) results showed that there were notable differences in microbial community composition related to plant compartments. Different networks based on plant compartments exhibited distinct topological features. Additionally, the bulk soil and rhizosphere networks were more complex and showed higher centrality and connectedness than the three endosphere networks. These results strongly suggested that plant compartments, and not species, affect microbiome composition. Graphical abstract: uf0001